P2x7 Receptor in Dendritic Cells and Macrophages: Implications in Antigen Presentation and T Lymphocyte Activation - Garcia Huidobro-Toro, J; Bachelet-Norelli, V; Acuna-Castillo, C; Barrera-Ávalos, C (Multidisciplinary Digital Publishing Institute (MDPI), 2024)
The P2X7 receptor, a member of the P2X purinergic receptor family, is a non-selective ion channel. Over the years, it has been associated with various biological functions, from modulating to regulating inflammation. However, its emerging role in antigen presentation has captured the scientific community’s attention. This function is essential for the immune system to identify and respond to external threats, such as pathogens and tumor cells, through T lymphocytes. New studies show that the P2X7 receptor is crucial for controlling how antigens are presented and how T cells are activated. These studies focus on antigen-presenting cells, like dendritic cells and macrophages. This review examines how the P2X7 receptor interferes with effective antigen presentation and activates T cells and discusses the fundamental mechanisms that can affect the immune response. Understanding these P2X7-mediated processes in great detail opens up exciting opportunities to create new immunological therapies. © 2024 by the authors.